PENGARUH TIMES INTEREST EARNED RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSETS PADA PT INDOFOOD CBP SUKSES MAKMUR TBK PERIODE 2015-2024 - Meidsya Nabilla; Tri Wartono (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of the Times Interest Earned Ratio (TIER) and Total Asset Turnover (TATO) on Return on Assets at PT Indofood CBP Sukses Makmur Tbk for the period 2015-2024, both simultaneously and partially. This research is a descriptive analysis study using secondary data obtained from the annual financial reports of PT Indofood CBP Sukses Makmur Tbk for the 2015-2024 period. The data collection technique used in this study is the classical assumption test, which includes the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The data analysis technique in this study utilizes multiple linear regression analysis processed with SPSS 26. The results of this study indicate that the Times Interest Earned Ratio (TIER) and Total Asset Turnover (TATO) have a significant effect on Return on Assets. The Times Interest Earned Ratio variable has a significant partial effect on Return on Assets, with a t-statistic value greater than the t-table (3.156 > 2.36462) and a significance value of 0.016 < 0.05. Similarly, the Total Asset Turnover (TATO) variable has a significant partial effect on Return on Assets, with a t-statistic value greater than the t-table (3.709 > 2.36462) and a significance value of 0.008 < 0.05. Simultaneously, the Times Interest Earned Ratio (TIER) and Total Asset Turnover (TATO) have a significant effect on Return on Assets, with an F-statistic value greater than the F-table (46,637 > 4.76) and a significance value of 0.000 < 0.05.